Football in the Chronicles of Doctor Moacyr Scliar (Global Journal of Human-Social Science, 2024)
This text aims to demonstrate how social relationships and human behaviors are brought up by the doctor and writer Moacyr Scliar in his texts about football. Among the various textual genres produced by the author, chronicles stand out, short narratives with everyday themes in which humor, reflection and irony underlie. The main objective of this text is to identify how the author uses football in association with human behaviors and considerations about health.
Keywords: moacyr scliar; medicine; chronicles; soccer